GhWRKY6 Acts as a Negative Regulator in Both Transgenic Arabidopsis and Cotton During Drought and Salt Stress - Li, Zhi; Li, Lei; Zhou, Kehai; Zhang, Yihao; Han, Xiao; Din, Yanpeng; Ge, Xiaoyang; Qin, Wenqiang; Wang, Peng; Li, Fuguang; Ma, Zhiying; Yang, Zhaoen (Frontiers in Genetics, 2019)
Drought and high salinity are two key limiting factors for cotton production. Therefore, more and more research is focused on the underlying stress response mechanisms of cotton. We first identified and cloned a novel gene encoding the 525 amino acid in cotton, namely GhWRKY6. Quantitative RT-PCR analysis indicated that GhWRKY6 was induced by NaCl, PEG and ABA. Analysis of germination rate and root length indicated that overexpression of GhWRKY6 in Arabidopsis resulted in plant being hypersensitive to ABA, NaCl and PEG treatment. In contrast, the loss-of-function mutant wrky6 was insensitive and had slightly longer roots than wild-type under these treatment conditions. We found that GhWRKY6 overexpression in Arabidopsis modulated salt- and drought-sensitive phenotypes and stomatal aperture by regulating ABA signalling pathways, as well as reduced plant tolerance to abiotic stress through the enrichment of reactive oxygen species (ROS), reduction of proline content, and increased electrolytes and malondialdehyde (MDA). The expression levels of a series of ABA-, salt- and drought-related marker genes were altered in OE, and wrky6 mutant lines. Using Virus-induced gene silencing (VIGS) technology, we verified that down-regulation of GhWRKY6 increased salt tolerance in cotton. These results demonstrate that GhWRKY6 is a negative regulator of plant responses to abiotic stress via the ABA signalling pathway.